2017
DOI: 10.1590/abd1806-4841.20175899
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of long term treatments of type I hereditary angioedema in a Turkish family

Abstract: BackgroundHereditary angioedema is a rare autosomal dominantly inherited immunodeficiency disorder characterized by potentially life-threatening angioedema attacks.ObjectiveWe aimed to investigate the clinical and genetic features of a family with angioedema attacks.MethodsThe medical history, clinical features and C1-INH gene mutation of a Turkish family were investigated and outcomes of long-term treatments were described.ResultsFive members had experienced recurrent swellings on the face and extremities tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Evidence of the HAE-GI symptom overlap comes from both observational 57 and single-case studies 27,38,42,50,[67][68][69][70] (Table 2). HAE should be suspected when a patient presents with a history of recurrent cutaneous angioedema attacks.…”
Section: When Should Hae Be Suspected? Practical Guidancementioning
confidence: 99%
“…Evidence of the HAE-GI symptom overlap comes from both observational 57 and single-case studies 27,38,42,50,[67][68][69][70] (Table 2). HAE should be suspected when a patient presents with a history of recurrent cutaneous angioedema attacks.…”
Section: When Should Hae Be Suspected? Practical Guidancementioning
confidence: 99%
“…New mutations are being defined every day, original research is reported from around the world, and new techniques are applied, providing improved understanding of the disease. [34,37,38] Next-generation sequencing has been used to study the genotype in C1-INH-HAE, and it has revealed that most [34] Relevant studies from our country [39] have been conducted and heterozygous mutations have been described in the 7 th exon (p.Leu416X [c.1247T> A]) by Akoglu et al [40] and by Büyüköztürk et al [41] in the promoter region (CAAT box, c.−101A>G). Ozkars et al [42] reported c. 601A>T nonsense variant mutation in the SERPING1 gene in C1-INH HAE patients.…”
Section: Serping1 Genementioning
confidence: 99%